Gastric acid secretion and risk of recurrence of duodenal ulcer within six to eight years after truncal vagotomy and drainage. Issue 9 (September 1974) - Kronborg, O.
Abstract : The value of insulin and augmented histamine tests in predicting recurrence of duodenal ulcer within six to eight years after truncal vagotomy and drainage was assessed in a series of 500 consecutively and electively operated patients. Criteria of recurrence were established by a discriminative analysis of gastric acid secretion parameters. Recurrence was predicted with a probability of about 75% in patients with dyspepsia, the proportion between recurrences and dyspeptic nonrecurrences being 1:1. The discriminatory ability of the insulin test was no better than that of the postoperative histamine test. Men with a preoperative PAO > 46·1 m-equiv/h had a risk of recurrence of 21%, women with a PAO > 41·5 m-equiv/h, 28%. Below these levels the risk was 5 and 1% respectively, demonstrating that recurrence after vagotomy is related to the number of parietal cells before vagotomy. A rationale is provided for antrectomy and vagotomy in duodenal ulcer patients with a high number of parietal cells.